1997
DOI: 10.1681/asn.v85720
|View full text |Cite
|
Sign up to set email alerts
|

Renal expression of monocyte chemoattractant protein-1 in lupus autoimmune mice.

Abstract: Mononuclear cell infiltration in glomeruli and renal interstitium is a prominent feature of some types of glomerulonephritis, including lupus nephritis. The mechanism(s) underlying monocyte influx into the kidney is not fully understood. Recently, monocyte chemoattractant protein-1 (MCP-1) has been identified as a chemotactic factor involved in the recruitment of monocytes/macrophages in the glomeruli of rats with mesangioproliferative as well as anti-glomerular basement membrane glomerulonephritis. In the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(10 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…MCP-1 is a monocyte chemotactic factor that binds CCR2 on monocytes and promotes monocyte mobilization from bone marrow, recruitment to local tissues, and differentiation into macrophages ( 73 , 90 ). MCP-1 has been implicated in inflammation and kidney diseases ( 73 , 75 , 79 , 91 ). CXCL10 is also increased after injury in Ret UB del kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCP-1 is a monocyte chemotactic factor that binds CCR2 on monocytes and promotes monocyte mobilization from bone marrow, recruitment to local tissues, and differentiation into macrophages ( 73 , 90 ). MCP-1 has been implicated in inflammation and kidney diseases ( 73 , 75 , 79 , 91 ). CXCL10 is also increased after injury in Ret UB del kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Timp-1, MCP-1, CXCL10, and IL-1ra were significantly higher in gent-exposed Ret UB del kidneys compared to gentamicin-exposed littermates with normal nephron number (Figure 7). Given that Timp-1, MCP-1 and CXCL10 have all been implicated in renal inflammatory diseases (64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79), we focused on these cytokines for further analysis. We found that while both control and Ret UB del mice had significantly increased expression of Timp-1 and MCP-1 after gentamicin, the increase was much greater in Ret UB del mice.…”
Section: Ret Ub Del Mice Have a Unique Inflammatory Response To Genta...mentioning
confidence: 99%
“…MCP-1 is induced by type I interferons and multiple pro-inflammatory cytokines ( 38 ). MCP-1 has potent chemiotactic activity, especially for macrophages and neutrophils ( 39 41 ), and thus may act to promote leucocyte recruitment to the kidney. Consistent with this possibility, it was shown to increase prior to proteinuria in LN flares ( 42 ) and higher levels are associated with worse clinical outcomes ( 20 , 42 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 is produced by tubular epithelial cells resulting in increased cytokine and adhesion molecule expression which further activates tubular epithelial cells, increasing the inflammatory response [ 65 ]. Animal models of SLE have demonstrated the role of MCP-1 as a driver of inflammatory cell infiltration and have suggested a potential therapeutic target role, as MCP-1 deletion reduced renal inflammation and proteinuria, and prolonged survival [ 67 , 68 ]. As a urinary biomarker, MCP-1 level has been demonstrated to increase in JSLE LN flares, to be a fair-good predictor of LN activity and to be higher in non-responders to therapy [ 44 , 45 , 48 , 50 , 54 ].…”
Section: Renal Biomarkersmentioning
confidence: 99%